Kedudukan dan Yurisdiksi Peradilan Militer di Indonesia - Irman Putra; Arief Fahmi Lubis (MIMBAR ADMINISTRASI FISIP UNTAG Semarang, 2021)
The discussion on the position and jurisdiction of the military judiciary in Indonesia is very important considering that it can always change according to the development of society. By knowing the historical background and mental conditions when the laws and regulations that govern these problems were made, it is hoped that research on military justice in Indonesia will become more comprehensive. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that history will have the same interpretation as regulated in the laws and regulations.